PENGARUH PERIKLANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI E-COMMERCE. - karnadi karnadi; Winny Lian Seventeen (Jurnal Ilmu Akuntansi, 2021)
This study aims to examine the effect of advertising and price on purchasing decisions in e-commerce. This research was conducted on students of the Faculty of Economics and Business, Unihaz. The number of samples in this study were 71 respondents. The results showed that 65.4% of the advertising and price variables were able to explain the purchasing decision variables in e-commerce. Based on the results of the simultaneous test, advertising and price variables affect purchasing decisions in e-commerce, while based on a partial test, advertising variables affect purchasing decisions in e-commerce. market, but price has no effect on purchasing decisions in e-commerce.